Enzymatic Phorbol Esters Degradation using the Germinated Jatropha Curcas Seed Lipase as Biocatalyst: Optimization Process Conditions by Response Surface Methodology - Avita Kusuma Wardhani; Chusnul Hidayat; Pudji Hastuti (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2016)
Utilization of Jatropha curcas seed cake is limited by the presence of phorbol esters (PE), which are the main toxic compound and heat stable. The objective of this research was to optimize the reaction conditions of the enzymatic PE degradation of the defatted Jatropha curcas seed cake (DJSC) using the acetone-dried lipase from the germinated Jatropha curcas seeds as a biocatalyst. Response Surface Methodology (RSM) using three-factors-three-levels Box-Behnken design was used to evaluate the effects of the reaction time, the ratio of buffer volume to DJSC, and the ratio of enzyme to DJSC on PE degradation. The results showed that the optimum conditions of PE degradation were 29.33 h, 51.11 : 6 (mL/g), and 30.10 : 5 (U/g cake) for the reaction time, the ratio of buffer volume to DJSC, and the ratio of enzyme to DJSC, respectively. The predicted degradation of PE was 98.96% and not significantly different with the validated data of PE degradation. PE content was 0.035 mg/g, in which it was lower than PE in non-toxic Jatropha seeds. The results indicated that enzymatic degradation of PE might be a promising method for degradation of PE.